Neargeodesics in Gromov hyperbolic John domains in Banach spaces - Allu, Vasudevarao; Pandey, Abhishek (Annales Fennici Mathematici, 2024)
In this paper, we prove that neargeodesics in Gromov hyperbolic John domains in Banach space are cone arcs. This result gives an improvement of a result of Li (2014).